El derecho a reusar los datos personales ante las entidades del sector público (Forseti. Law Review, 2025)
The article examines whether the reuse of personal data, through portability, can be required of Peruvian public entities. It analyzes the concepts of portability and interoperability, current regulations, public and private digital services, and the new Regulation of Law No. 29733, proposing an interpretation aligned with the personal data protection regime in the public sector.
Keywords: Personal data; informational self-determination; portability; interoperability; digital transformation; digital government; digital services